Immunomodulatory and Antiviral Activity of Metformin and Its Potential Implications in Treating Coronavirus Disease 2019 and Lung Injury - Chen, Xianyang; Guo, Huifang; Qiu, Li; Zhang, Chengdong; Deng, Qiang; Leng, Qibin (Frontiers in Immunology, 2020)
The pandemic of involving coronavirus disease 2019 (COVID-19), which causes severe lung injury and multiple organ damagesdamage, presents an urgent need for new drugs. The case severity and fatality of COVID-19 are associated with excessive inflammation, namely, a cytokine storm. Metformin, a widely used drug to treat type 2 diabetes mellitus and metabolic syndromes, has the immunomodulatory activity to that reduces the production of pro-inflammatory cytokines by macrophagemacrophages as well as the formation of neutrophil extracellular traps (NETs). Metformin also inhibits the cytokine production of pathogenic Th1 and Th17 cells. Importantly, treatment ofwith metformin alleviates various lung injuries in pre-clinicalpreclinical animal models. FurthermoreIn addition, a recent proteomic study has revealed that metformin has the potential to directly inhibit SARS-CoV-2 infection, Furthermore, retrospective clinical studies have revealed that metformin treatment reduces the mortality of type 2 diabetic patients with COVID-19. Therefore, metformin has athe potential to be repurposed to treat patients with COVID-19 patients at risk to developof developing severe illness. This review addresses summarizes the immune pathogenesis of SARS-CoV-2 and addresses the effects of metformin on inhibiting cytokine storm and preventing SARS-CoV-2 infection, as well as its side effects.